Seed invigoration for improved field performance and storability in ash gourd (Benincasa hispida (Thunb.) Cogn.) - Bennett Thomas.K (Department of Seed Science and Technology, College of Horticulture, 2019)
Ageing of seeds is an inevitable natural phenomenon, subsequently resulting in loss of vigour and viability. Adopting appropriate packaging, ensuring optimum storage environment and priming ash gourd seeds was found to be beneficial in slowing down the pace of the deteriorative process during storage, maintaining the seed quality and prolonging seed longevity. Despite the improvements in seed performance following priming treatments, there have been contrasting reports on its impact on seed storage potential and crop performance. Considering the above, a study to elucidate the effect of seed priming on field performance in ash gourd variety KAU Local and to assess the impact of packing material on seed quality and longevity, was conducted at College of Horticulture, Vellanikkara, Thrissur, during 2016 - 2019. The effect of seed invigouration and packing material on seed viability and seed quality parameters under ambient storage environment was assessed following a completely randomized design with three replications and seven priming treatments (I1 to I7). Freshly extracted seeds were separately primed using CaCl2 (50 mM) for 12 h (I1), CaCl2 (50 mM) for 24 h (I2), kinetin (10 ppm) for 12 h (I3), kinetin (10 ppm) for 24 h (I4), KH2PO4 (10-1 M) for 24 h (I5) and Psuedomonas fluorescens (1×106 cfu.ml-1) for 12 h (I6). Untreated seeds (I7) served as control. Both treated and untreated seeds were dried to ≤ 8 per cent moisture content and packed in polyethylene 700 gauge pouches (P1: Poly 700G pouches) and in aluminium laminated pouches (P2: Al. pouches). The seed quality parameters were recorded after treatment from the start of storage and at monthly intervals for a period of six months of storage (MAS). At bimonthly intervals, quantification of lipid peroxidation, sugar and amino acids leached out from the seeds were also done. In addition, the performance of crop raised from seeds, stored for five months and subjected to priming just prior to sowing (T1: Pre-sowing treatment) and prior to storage (T2: Pre-storage treatment), was also assessed following a randomized block design with three replications and seven priming (I1 to I7) treatments as detailed in the laboratory studies. The fruit as well as seed yield parameters were recorded from the crop raised. Results of storage studies revealed that irrespective of the packaging material, germination and vigour indices I and II in both treated and untreated seeds decreased progressively over the storage period. However, there was an increase in and lipid peroxidation, electrical conductivity of seed leachate, leachate of sugar and amino acid towards the end of storage period. Irrespective of the invigouration treatment and the storage period, storing seeds either in Poly 700 G pouches (P1) or Al. pouches (P2) did not influence seed viability, vigour (VI-I), moisture content and lipid peroxidation in packed seeds. Considering the influence of invigouration treatment alone, priming seeds with kinetin 10 ppm either for 12 h or 24 h or biopriming seeds (P. fluorescens 1 × 106 cfu ml-1 12 h) or storing them untreated, was found to be the best. Existence of a strong influence of the interaction between packing material, invigouration treatment and storage period on seed quality and longevity of packed seeds was discerned. Under ambient storage environment (72% RH and 32 0C), it would be best to pack seeds in aluminium foil pouches after invigouration with P. flourescens 1 × 106 cfu ml-1 for 12 h (P2I6), as this was found to prolong seed longevity the farthest i.e., until five months after storage (5 MAS). However, the bioprimed seeds if stored in polyethylene 700G pouches (P1I6) had retained viability above the minimum standards of seed certification (MSCS) for 4 MAS only. Similar to P1I6, storing untreated seeds in polyethylene (P1I7) or seeds primed with CaCl2 50 mM for 24 h in polyethylene 700G pouches (P1I2) retained viability above MSCS for 4 MAS. However, storing them in Al. pouches (P2I7 and P2I2) was less effective. From the results of the field experiment it was evident that administering the seed treatment prior to sowing i.e., as a pre-sowing treatment was more beneficial for plant growth and yield, rather than applying the same as a pre-storage treatment. Seed yield per fruit on dry weight basis was the highest (I7: 12.10 g) when the crop was raised from unprimed seeds [(both pre-sowing (T1I7: 12.15 g) and pre-storage (T2I7: 12.05g)], while the fruit yield per vine from unprimed seeds ranged between 7.01 kg (T1I7) and 7.08 kg (T2I7). In addition, the production of female flowers was observed to be the earliest (I7: 93.67 days; T1I7: 95.00 days and T2I7: 92.33 days) in the crop raised from untreated seeds. The single fruit weight (I7: 2.12 kg; T1I7: 2.01 kg and T2I7: 2.22 kg) and 100-seed weight (I7: 4.67 g T1I7: 4.53 g and T2I7: 4.80 g), were also high on using untreated seeds. Pre-sowing priming seeds with KH2PO4 10-1 M 24 h (I5) had registered the highest fruit yield per vine (T1I5: 7.64 kg), although the weight of single fruits in this treatment (1.65 kg) was less than that observed in untreated seeds (2.01 kg to 2.22 kg). This was attributed to the higher number of fruits per vine (4.63 Nos.) produced in KH2PO4 primed seeds compared to untreated seeds (3.19 Nos. to 3.49 Nos.) The seed yield per fruit in KH2PO4 10-1 M 24 h primed seeds (I5: 8.37 g; T1I5: 7.93 g and T2I5: 8.80 g) was the highest, next to using unprimed seeds. Hence, considering the impact of priming treatment, time of seed priming and their interaction, it was evident that using untreated seeds was most advantageous to raise a seed crop from aged seeds. However, pre-sowing seed priming of aged seeds with KH2PO4 10-1 M 24 h would help realise better fruit yield per vine.